2022
DOI: 10.1038/s41598-022-11642-6
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The numerical study of pressure and temperature effects on mechanical properties of baghdadite-based nanostructure: molecular dynamics simulation

Abstract: Bioceramics have been commonly implemented to replace and restore hard tissues such as teeth and bones in recent years. Among different bioceramics, Baghdadite (BAG) has high bioactivity due to its ability to form apatite and stimulate cell proliferation. So, this structure is used widely for medical applications to treat bone-based diseases. Physically, we expect changes in temperature and pressure to affect the Baghdadite-based nanostructure’s mechanical behaviour. So, in this computational study, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…1. using the location factor defined for the price area (Brovelli et al, 2016); 2. using the cost response surface to the location of valuation objects (Trnka et al, 2011); 3. using the distance values (distance ranges) from the objects of influence (price factors) of the valuation objects (Liu, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…1. using the location factor defined for the price area (Brovelli et al, 2016); 2. using the cost response surface to the location of valuation objects (Trnka et al, 2011); 3. using the distance values (distance ranges) from the objects of influence (price factors) of the valuation objects (Liu, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when stressed by applied force or high temperatures, the tilted structure transforms into a severely distorted structure. 47 Moreover, Liu et al observed that the potential energy of the Pb–I bond is highly anharmonic. 48 Again, the large amplitude of I atom vibrations causes strong lattice deformation at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, Liu et al. [ 122 ] investigated the influence of temperature and pressure variations on the mechanical conductivity of the baghdadite matrix with nanoscale dimensions using the MD method.…”
Section: Applications Of Baghdadite Ceramicmentioning
confidence: 99%
“…The increase in pressure and temperature at the beginning of the process will decrease the mechanical properties of nanostructures. In clinical applications, the initial condition must be considered when examining the mechanical behavior of baghdadite-based nanostructures [ 122 ].…”
Section: Applications Of Baghdadite Ceramicmentioning
confidence: 99%